2002
DOI: 10.1097/00008469-200210000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of MCF-7 human breast cancer cells by progesterone is associated with cell differentiation and phosphorylation of Akt protein

Abstract: Progesterone inhibits the proliferation of normal breast epithelial cells as well as breast cancer cells. The molecular mechanisms of this inhibition are not fully understood. The purpose of this study was to investigate the capacity of progesterone to induce apoptosis and to alter the activity of a key regulator of cell growth and differentiation, the Akt protein. We show here that (i) growth inhibition of breast cancer cells by progesterone is due to the induction of cell differentiation and not to apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Although a slight increase in cell growth was already found after incubation with P4 alone, the presence of E2 resulted in increased proliferation. These findings are in agreement with the literature, which previously demonstrated that P4 in MCF7 cells enhanced primarily differentiation whereas proliferation was mainly caused by E2 [Alkhalaf et al, 2002]. Nevertheless, the gene expression profile of MCF7 cells previously treated with P4 alone comprised genes involved in cell cycle and DNA repair.…”
Section: Discussionsupporting
confidence: 93%
“…Although a slight increase in cell growth was already found after incubation with P4 alone, the presence of E2 resulted in increased proliferation. These findings are in agreement with the literature, which previously demonstrated that P4 in MCF7 cells enhanced primarily differentiation whereas proliferation was mainly caused by E2 [Alkhalaf et al, 2002]. Nevertheless, the gene expression profile of MCF7 cells previously treated with P4 alone comprised genes involved in cell cycle and DNA repair.…”
Section: Discussionsupporting
confidence: 93%
“…Depending on growth factors/cytokine-signaling pathways, which are specific to and different in each cell line, the cell fate induced by progesterone may be different: growth inhibition or proliferation. In conditions similar to ours, other studies also indicated that progestininduced growth inhibition coincides with enhancement of differentiation in various mammary cell lines, including T-47D (Kester et al, 1997;Alkhalaf et al, 2002;Lin et al, 2003). In all cases, all these hormonal effects on proliferation and/or differentiation appear to be completely independent of the protective effect of the hormone against radiation-induced apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…In studies showing that progesterone mediated growth inhibition via apoptosis induction (Formby and Wiley, 1998;Gompel et al, 2000), overall the rate of apoptosis was very low and, more importantly, the hormone was used at a high and nonphysiological concentration. Using physiological ranges of progesterone concentrations (1-100 nM), we and others (Ory et al, 2001;Alkhalaf et al, 2002) showed a significant protective effect of progesterone against apoptosis. Moreover, in standard conditions of culture, we failed to observe any difference in the rate of cell death in unirradiated cells with or without progesterone treatment (Figure 3).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations